DETERMINAN MINAT PEMAKAIAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) - Menny Sri Murniaty Saragih; Heru Santoso; Friska Sitorus; Kesaktian Manurung; Taruli R Sinaga (HUMAN CARE JOURNAL, 2023)
Intrauterine contraception (IUD), an effective, safe, and reversible long-term contraceptive, is made of small plastic or metal of various sizes and is inserted into the uterus. The IUD has very high efficacy with 0.6 to 0.8 pregnancies per 100 women using the IUD with 1 failure in 125 to 170 pregnancies. it is known that the achievement of IUD use is still low, namely only 7.4% of a total of 10,536 PUS. The aim of the study was to analyze the determinants of interest in using contraceptives in the working area of the Puskesmas. This type of analytic observational research uses a cross sectional approach. This research was conducted in January-June 2022. The sample size was 33 PUS women who participated in active family planning. The results showed that predisposing factors (perceptions) had an effect on interest in using the IUD. Enabling factors (access to information, availability of IUDs, and competence of staff) did not influence intention to use IUDs and reinforcing factors (support of health workers) did influence intentions to use IUDs. It is recommended to the community, it is hoped that they can provide good and straightforward services so that PUS is interested in installing the IUD and can discuss and consult directly with health workers regarding the KB they want to use.